Optimising medical retrieval processes and outcomes in remote areas in high‐income countries: A scoping review. (19th July 2022) - Mathew, Supriya; Russell, Deborah J.; Fitts, Michelle S.; Wakerman, John; Honan, Bridget; Johnson, Richard; Zhao, Yuejen; Reeve, David; Niclasen, Petra
Abstract: Objective: This scoping review explores the structure and process‐level strategies that are associated with medical retrieval outcomes. A secondary aim is to identify the range of medical retrieval outcomes used to assess the performance of remote retrieval services. Design: A scoping review of peer‐reviewed literature from PubMed, CINAHL and the Web of Science was undertaken following guidelines set by the Johanna Briggs Institute manual for scoping reviews. All articles were assessed by two reviewers. Themes were derived inductively from the data extracted. Setting: Medical retrievals in sparsely populated remote locations in high‐income countries. Participants: Staff and clients of remote medical retrieval services. Interventions: Structures and processes (e.g. resource availability, retrieval staff structures and governance protocols) that aimed to improve medical retrieval outcomes. Outcomes: Patient health outcomes and service efficiency. Results: Twenty‐four articles were included. Three broad themes, related to the nature of the interventions, were included: optimising prehospital management of retrievals, staffing and resourcing of retrieval services and retrieval model evaluation. Mortality was the most frequently used outcome indicator in these studies, but was not measured consistently across studies. Conclusions: This review highlights significant gaps in the literature that describes the structure and processes of retrieval models operating in remote areas and a dearth of literature evaluating specific operational strategies implemented within medical retrieval models. The available literature does not meaningfully assist with identifying key outcome indicators for developing a consistent monitoring and evaluation framework for retrieval services in geographically, culturally and demographically diverse remote contexts.